IMPROVING THE PSYCHOLOGY OF LEADERS IN PUBLIC ADMINISTRATION (IN THE CASE OF MILITARY PERSONNEL) - Ismatov Farkhod Aslidinovich (Web of Journals Publishing, 2024)
This article describes the psychology of leadership in military personnel and its specific aspects.
Keywords: Leader, psychology of a military leader, leadership ethics and behavior, abilities, commands.